Africa and the ICC : perceptions of justice / edited by Kamari M. Clarke, Abel S. Knottnerus and Eefje de Volder. - Clarke, Kamari Maxine, 1966-; Knottnerus, Abel S.; Volder, Eefje de (Cambridge University Press, 2016)
Africa and the ICC: Realities and Perceptions comprises contributions from prominent scholars of different disciplines including international law, political science, cultural anthropology, African history and media studies. This unique collection provides the reader with detailed insights into the interaction between the African Union and the International Criminal Court (ICC), but also looks further at the impact of the ICC at a societal level in African states and examines other justice mechanisms on a local and regional level in these countries. This investigation of the ICC's complicated relationship with Africa allows the reader to see that perceptions of justice are multilayered.